Eye, Ear, Nose, Throat or Mouth (Eent) Healthcare Associated Infections in A Tertiary Care Pediatric Icu - Singh, Shubham Prakash; Randhawa, V.S.; Gupta, Shalu; Singh, Gautam Bir (Journal of Neonatal Surgery, 2025)
Background: Healthcare-associated infections (HAIs) remain a major challenge in critical care settings, especially in pediatric intensive care units (PICUs). While a considerable body of literature has investigated respiratory, bloodstream, and urinary tract HAIs, limited attention has been paid to EENT (eye, ear, nose, throat or mouth) infections in children. EENT HAIs can lead to prolonged hospital stays, increased healthcare costs, and significant morbidity, warranting a focused exploration of their etiological agents, associated risk factors, and outcomes. Methods: A prospective observational study was conducted from May 2023 to November 2024 in the PICU of Kalawati Saran Children’s Hospital, New Delhi. One hundred and twenty-five (125) pediatric patients aged 1 month to 18 years, admitted for at least 48 hours, were screened for EENT HAIs. Microbiological investigations and antimicrobial susceptibility testing were carried out using standard culture methods and automated systems. Relevant risk factors, including demographic variables, comorbidities, and invasive procedures, were analyzed through univariate logistic regression. Results: Of 125 enrolled cases, 11 developed EENT HAIs, yielding an infection rate of 8.8 per 100 admissions. Ear infections were predominantly caused by Acinetobacter baumannii and Klebsiella pneumoniae, while Staphylococcus aureus (MRSA) was isolated from nasal specimens. Pseudomonas aeruginosa was a frequent pathogen in throat infections. Susceptibility testing revealed significant resistance patterns, particularly among Acinetobacter baumannii and carbapenem-resistant Enterobacterales. Although 45.4% (n=5) of EENT HAI cases underwent invasive procedures, no single risk factor reached statistical significance (p<0.05). Five children required mechanical ventilation or central line placement; one case succumbed to multi-organ dysfunction. Conclusion: EENT HAIs in PICUs, though less frequently reported than other HAIs, require heightened vigilance due to the involvement of multidrug-resistant organisms. Strict adherence to infection control protocols, judicious antimicrobial use, and prompt microbiological diagnosis are essential to improve outcomes.